TINJAUAN YURIDIS TERHADAP TINDAKAN PIDANA BULLYING SERTA DAMPAKNYA DI LINGKUNGAN SEKOLAH - Muhamad Zacky Wiby Piandy; Rocky Alexsandro Oktamora Manurung; Yarfis Andika; Dede Ika Murofikoh (JURNAL ILMIAH NUSANTARA, 2026)
Bullying is a type of negative behavior frequently encountered in schools and has the potential to lead to legal consequences as it can be considered a crime. This research aims to analyze criminal acts of bullying from a legal perspective and their effects in the educational environment based on applicable regulations in Indonesia. The methodology used in this study is normative legal research with a legislative and conceptual approach. Data collection was carried out through a literature review of primary, secondary, and tertiary legal sources. The results of this study indicate that acts of bullying, whether physical, verbal, or psychological, meet the criteria for criminal offenses in accordance with the provisions of the Criminal Code and Law No. 35 of 2014 concerning Child Protection. The effects of bullying in schools include mental health issues, a decline in academic performance, and the formation of an unsupportive educational atmosphere. Therefore, there is a need for enhanced law enforcement and active involvement of educational institutions in preventing and addressing bullying to ensure the protection of children's rights.